Física de sabores e modelos multi-Higgs - Correia, Fagner Cintra [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The minimal 331 model has been proposed as an extension of the Standard Model based on the gauge group SU'(3) IND. L' ?U'(1) IND.X'. In this model, the left-handed fermions transform as triplets (or anti-triplets) under the action ofSU'(3) IND. L', whose generations correspond to the known SM fermions and new heavy quarks. Our purpose here is to constrain the 331 parameters considering the limits of ?avour changing processes as meson mixing

O modelo331 mínimo consiste em uma extensão ao Modelo Padrão amparada em SU'(3) IND.L' ? U'(1) IND. X'. Os férmions se transformam como tripletos ou anti-tripletos de SU'(3) IND. L' com componentes envolvendo quarks exóticos e partículas conhecidas da fenomenologia atual. Nosso objetivo aqui é explorar qualidades adicionais e limitar novos parâmetros do 331 a partir de processos que violem sabor, como a mistura de mésons neutros
Keywords: Partículas (Física nuclear); Quarks; Higgs, Bosons de; Flavordinamica quantica; Partículas (Física nuclear) - Sabor